Femifesta? Reflections on writing a feminist memoir and a feminist manifesto. Issue 4 (7th June 2017) - David, Miriam E.
ABSTRACT: This is a reflective account of the publication of two books in the same year (2016): Reclaiming Feminism: Challenging Everyday Misogyny and Feminist Manifesto for Education . The former is a popular but scholarly memoir, and the latter is an academic text for sociology and education. It was never my intention to publish one, let alone, two books but I was spurred to do so by the prevailing socio-political and cultural climate: what I now see clearly as everyday misogyny.